New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from Croatia - Karaman, Gordan S.; Sket, Boris (Zootaxa, 2019)
New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from the subterranean waters of cave Lubuška jama near Hajdučki Kukovi in the western part of Velebit Mt. in Croatia, is described and figured, and its relations to other genera and species of the family Niphargidae is discussed. The new taxon is a small niphargid, similar to Niphargobates. The list of all known genera of family Niphargidae is given and key to the genera of this family is presented.